The Braided Dream : Robert Penn Warren's Late Poetry - Runyon, Randolph, 1947- (Book collections on Project MUSE., 1990)
Robert Penn Warren's reputation as a poet, though always considerable, has soared in the last decade, as indicated by his recent selection as America's first poet laureate. The Braided Dream is one of the first book-length studies of the poetry that has led to Warren's recent rise to eminence and the first to consider his final collection, Altitudes and Extensions. In a communicable, jargon-free style that will appeal to the nonacademic reader as well as the serious scholar, Randolph Paul Runyon provides a detailed and illuminating guide to a body of poetry that, despite its greatness, has un.